Accelerated loop-mediated isothermal amplification method for the rapid detection of Streptococcus suis serotypes 2 and 14 based on single nucleotide polymorphisms - Meng, Jiajia; Li, Chunling; Wang, Yu; Bian, Zhibiao; Chu, Pinpin; Zhai, Shaolun; Yang, Dongxia; Song, Shuai; Li, Yan; Jiang, Zhiyong; Zhang, Kunli; Li, Yugu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Streptococcus suis serotypes 2 and 14 the most prevalent zoonotic strains. The establishment of a sensitive and extremely accurate method for point of care testing of Streptococcus suis serotype 2 and 14 strains on-site is highly desired. In this study, a loop primer probe-introduced loop-mediated isothermal amplification assay was developed to differentiate Streptococcus suis serotype 2 and 14 based on SNP. The specific fluorescent probes were designed for the SNP site specific for serotype 2 and 14 Streptococcus suis cpsK genes, and the loop primer probe-introduced loop-mediated isothermal amplification assay was developed using the specific cleavage properties of RNase H2 enzyme. Accelerated speed and efficiency of LAMP assays through the use of swarm primers (LF primer and F0 primer). It showed that the amplification reaction can be performed efficiently at isothermal 59°C. The resuts can be real time detected or judged by using a smartphone and a 3D printed visualization cassette. The sensitivity of the Streptococcus suis LAMP assay can reach 18.4 CFU within 40 minutes. The detection rate of the assay system was evaluated using clinical 19 samples with suspected Streptococcus suis infection, and the detection rate was consistent with the sequencing method, which is highly practical. The LAMP assay for Streptococcus suis established in this study has strong specificity, high sensitivity and simple operation, while the reaction can be performed at isothermal temperature, is not dependent on instruments, professional operators and is suitable for field testing.